Prevalence and correlates of depression and alcohol use disorder among adults attending primary health care services in Nepal: a cross sectional study - Nagendra P. Luitel; Emily C. Baron; Brandon A. Kohrt; Ivan H. Komproe; Mark J. D. Jordans (BMC, 2018)
Abstract Background Although depression and alcohol use disorder (AUD) are expected to be common among patients presenting to primary health care setting, there is limited research on prevalence of depression and AUD among people attending primary health care services in low-income countries. The aim of this study was to assess the prevalence of depression and AUD among adults attending primary care facilities in Nepal and explore factors associated with depression and AUD. Methods We conducted a population-based cross-sectional health facility survey with 1474 adults attending 10 primary healthcare facilities in Chitwan district, Nepal. The prevalence of depression and AUD was assessed with validated Nepali versions of the Patient Health Questionnaire (PHQ-9) and Alcohol Use Disorder Identification Test (AUDIT). Results 16.8% of the study sample (females 19.6% and males 11.3%) met the threshold for depression and 7.3% (males 19.8% and females 1.1%) for AUD. The rates of depression was higher among females (RR = 1.48, P = 0.009), whereas rates of AUD was lower among females (RR = 0.49, P = 0.000). Rates of depression and AUD varied based on education, caste/ethnicity, occupations and family income. Conclusions In Nepal, one out of five women attending primary care services have depression and one out of five men have AUD. Primary care settings, therefore, are an important setting for detection and treatment initiation for these conditions. Given that "other" occupation is at increased risk for both conditions, it will be important to assure that treatments are feasible and effective for this high risk group.